C188‐9 reduces TGF‐β1‐induced fibroblast activation and alleviates ISO‐induced cardiac fibrosis in mice - Jiao Liu; Yuxuan Jin; Bei Wang; Jinying Zhang; Shengkai Zuo (FEBS Open Bio, 2021)
Cardiac fibrosis is the final event of heart failure and is associated with almost all forms of cardiovascular disease. Cardiac fibroblasts (CFs), a major cell type in the heart, are responsible for regulating normal myocardial function and maintaining extracellular matrix homeostasis in adverse myocardial remodeling. In this study, we found that C188‐9, a small‐molecule inhibitor of signal transducer and activator of transcription 3 (STAT3), exhibited an antifibrotic function, both in vitro and in vivo. C188‐9 decreased transforming growth factor‐β1‐induced CF activation and fibrotic gene expression. Moreover, C188‐9 treatment alleviated heart injury and cardiac fibrosis in an isoproterenol‐induced mouse model by suppressing STAT3 phosphorylation and activation. These findings may help us better understand the role of C188‐9 in cardiac fibrosis and facilitate the development of new treatments for cardiac fibrosis and other cardiovascular diseases.